Plain paradise [large type] - Wiseman, Beth, 1962- (Wiseman, Beth, 1962- Daughters of the promise novel., 2010)
Josephine will discover more than she bargained for as her world collides with the Plain people of Lancaster County. Josephine Dronberger was a scared teenager when she left her baby in the care of an Old Order Amish couple. But seventeen years have passed and Josie longs to reconnect with her daughter. Linda--as the couple named the child--is promised to Stephen Ebersol, the bishop's grandson. They plan to marry in the fall. When her birth mother comes to Paradise, Linda is drawn to a world she's never known. Will the direction she's been heading since birth be suddenly derailed, and who will stand by her convictions--mother or daughter?